2010
DOI: 10.1161/hypertensionaha.109.147231
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and Oxidative Stress Strengthen the Association Between Myeloperoxidase and Blood Pressure

Abstract: Abstract-Scavenging of the vasodilator nitric oxide by myeloperoxidase activity in the vasculature may contribute to hypertension. Because hydrogen peroxide is a cosubstrate of myeloperoxidase, hyperglycemia-induced oxidative stress may strengthen the relationship between myeloperoxidase and blood pressure. We investigated this relationship and its modification by hyperglycemia and oxidative stress in a population-based cohort of elderly subjects with normal glucose metabolism (nϭ267), impaired glucose metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…In this sense, feeding the DSF during 6 weeks did not alter plasma oxLDL, indicating that oxidative stress is not increased during the intervention. Myeloperoxidase is an enzyme linked to both oxidative stress and inflammation, and may promote atherogenesis (22). Patients with type 2 diabetes have shown elevated levels of these molecules compared with non-diabetic population (23), and increasing myeloperoxidase levels were associated with greater progression of atherosclerosis in diabetic patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, feeding the DSF during 6 weeks did not alter plasma oxLDL, indicating that oxidative stress is not increased during the intervention. Myeloperoxidase is an enzyme linked to both oxidative stress and inflammation, and may promote atherogenesis (22). Patients with type 2 diabetes have shown elevated levels of these molecules compared with non-diabetic population (23), and increasing myeloperoxidase levels were associated with greater progression of atherosclerosis in diabetic patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…149,150 Plasma levels of asymmetric dimethylarginine (endothelial nitric oxide synthase inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. To further support a relationship between oxidative stress and blood pressure, Van et al 151 recently showed that myeloperoxidase is positively and independently associated with blood pressure and that this association is strongest in subjects with increased levels of oxidative markers. Phagocytic NADPH oxidase activity is increased in obese subjects, possibly due to hyperleptinemia, and is related to vascular remodeling and preclinical atherosclerosis, risk factors associated with hypertension.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…fasting. A positive correlation of MPO with FPG (Table 3) in IFG group indicates the role of high glucose concentrations in stimulating vascular production of MPO and its reactive oxygen species causing deleterious effects [23].…”
Section: Discussionmentioning
confidence: 97%